Transforming Agriculture: The Innovation Route to Competitiveness in an Agro-Exporter Company in Peru - Jacinto Olivera, Angie Stephanie; Cueva Olivera, Sarita Lizbhet; Zúñiga Abregú, Romi Rubí (LACCEI, 2025)
The objective of this study was to determine the influence of product, process, organization and marketing innovations on the competitive advantage of the Agricultural Corporation JJM S.A.C., located in Casma, Peru. The research used a quantitative approach, non-experimental-cross-sectional design and relational scope. Validated questionnaires were applied to the company's senior management, obtaining results that demonstrated a very significant relationship between the dimensions of innovation and competitiveness, with Pearson coefficients ranging between 0.891 and 0.968. The results highlighted that process improvement generated the most significant impact on competitiveness, by optimizing operations and reducing costs, followed by organizational innovation, which improved the internal structure and leadership practices. Product innovation allowed the company to diversify its offering and adapt to the demands of the global market, while marketing innovation, although less influential, strengthened the relationship with customers and the company's positioning. Furthermore, statistical analyses showed that these innovative activities have allowed the corporation to consolidate its position as one of the main mango agro-exporters in the region, highlighting its ability to adapt to a competitive global environment. In conclusion, innovative activities are essential to strengthen the competitiveness and promote the growth of Corporación Agrícola JJM S.A.C. in international markets. In this sense, this comprehensive approach to innovation reinforces its ability to face global challenges and consolidate itself as a relevant player in the Peruvian agro-export sector.